2005
DOI: 10.1002/cncr.21483
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of insulin‐like growth factor binding protein 1 and ferritin light polypeptide in gestational trophoblastic neoplasia

Abstract: Findings showed that reduced expression of genes related to cell invasion and immunosuppression, especially FTL and IGFBP1, were associated with development of GTN, and this finding may provide a better understanding of the pathogenesis of GTN. The potential application of FTL and IGFBP1 in management of patients with HM should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Evolved from the suppressive polymerase chain reaction (PCR) technique, SSH has a number of advantages, including ease, specificity, and the capacity to isolate low copy transcripts [10]. SSH has been successfully employed in studies of developmental biology, cancer, and immune regulation [11,12,13]. We report here the identification of a large number of genes differentially expressed during postnatal kidney development.…”
Section: Introductionmentioning
confidence: 99%
“…Evolved from the suppressive polymerase chain reaction (PCR) technique, SSH has a number of advantages, including ease, specificity, and the capacity to isolate low copy transcripts [10]. SSH has been successfully employed in studies of developmental biology, cancer, and immune regulation [11,12,13]. We report here the identification of a large number of genes differentially expressed during postnatal kidney development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, FTL was reported to be downregulated in gestational trophoblastic neoplasia. 32 However, so far neither FTL nor RPL18 nor ZIN have been implicated in glioma pathogenesis. The same applies for the spermidine synthase gene SRM, whose transcript levels were also lower in 1p/19q-deleted tumors.…”
mentioning
confidence: 99%
“…Insulin-like growth factor (IGF) I and II were found to be increased in placental tissues prior onset of clinical preeclampsia and fetal growth restriction [12]. It has been reported that molar pregnancies had also high levels of IGF II, insulin receptors and insulin-like growth factor binding protein I (IGFBP-1) compared with normal placenta tissues [13][14][15]. The autocrine or paracrine actions of IGF-II and IGFBP-1 may be especially important during implantation and trophoblast invasion [16].…”
Section: Discussionmentioning
confidence: 98%